Efeitos subletais da formulação comercial do herbicida 2,4-D em Physalaemus cuvieri (Anura: Leptodactylidae) - Santos, Gilcinéia dos (2020)
The water sources surrounding agricultural areas are highly exposed to contamination due to the flow of pesticides. The contamination of these water resources interferes in the dynamics of amphibian populations due to the fragility of these organisms to chemical substances. Amphibians are considered environmental bioindicators for their high sensitivity to pesticides and for integrating aquatic and terrestrial ecosystems. 2,4-D is the second best-selling herbicide in Brazil and has already been detected in surface and underground waters. It is recognized as one of the main pollutants of aquatic ecosystems for its bioaccumulation capacity in non-target organisms. In this scenario, the objective of this work was to evaluate the sublethal effects of different concentrations of the commercial formulation of 2,4-D in relation to mortality, swimming activity, malformations and genotoxic potential in Physalaemus cuvieri. P. cuvieri tadpoles were exposed to six concentrations of 2,4-D: 0.0, 4.0, 30.0, 52.5, 75.0 and 100.0 μg a.e. L-1, for 168 hours. Tadpoles showed changes in swimming activity, especially hyperactivity. Malformations in the mouth and intestine were the most frequently found alterations, being significant in the concentration of 100.0 μg a.e. L-1. The use of 2,4-D increased the frequency of the micronucleus in the highest tested concentrations, in addition to inducing other nuclear abnormalities such as lobed nucleus, notched nucleus, bubble nucleus and microcytosis nucleus. The mortality was significant in concentrations above 52.5 μg a.e. L-1.These results demonstrate the commitment to the development and maintenance of the P. cuvieri species in its natural environments.